2012
DOI: 10.1242/bio.20122451
|View full text |Cite
|
Sign up to set email alerts
|

VPS35 regulates developing mouse hippocampal neuronal morphogenesis by promoting retrograde trafficking of BACE1

Abstract: SummaryVPS35, a major component of the retromer, plays an important role in the selective endosome-to-Golgi retrieval of membrane proteins. Dysfunction of retromer is a risk factor for neurodegenerative disorders, but its function in developing mouse brain remains poorly understood. Here we provide evidence for VPS35 promoting dendritic growth and maturation, and axonal protein transport in developing mouse hippocampal neurons. Embryonic hippocampal CA1 neurons suppressing Vps35 expression by in utero electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 46 publications
(71 reference statements)
5
78
0
Order By: Relevance
“…Modulating the localization of BACE1 in synaptic terminals is an alternative approach for decreasing amyloid deposition. Recent studies showed that either increased axonal transport of BACE1 by calsyntenin 1 (53) or retrograde transport by vps35 significantly altered amyloid deposition (56). Transgenic mice overexpressing RTN3 have reduced amyloid deposition (23,35,36,57), and this reduction is partially attributable to reduced BACE1 in presynaptic terminals in response to overexpression of RTN3 in mouse neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Modulating the localization of BACE1 in synaptic terminals is an alternative approach for decreasing amyloid deposition. Recent studies showed that either increased axonal transport of BACE1 by calsyntenin 1 (53) or retrograde transport by vps35 significantly altered amyloid deposition (56). Transgenic mice overexpressing RTN3 have reduced amyloid deposition (23,35,36,57), and this reduction is partially attributable to reduced BACE1 in presynaptic terminals in response to overexpression of RTN3 in mouse neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, VPS35 knockdown (KD) in mouse embryonic hippocampal neurons results in shortened apical dendrites, reduced dendritic spines and swollen commissural axons [97].…”
Section: Evidence For a Developmental Component Of Pd: Deregulated Emmentioning
confidence: 99%
“…Little is known about the role of VPS35 in neurogenesis partly because homozygous KO mice die early during embryonic development, before E10 and before the onset of neurogenesis [231]. In one study focusing on Alzheimer's disease by Wang et al [97], VPS35 was shown to promote apical dendritic growth and maturation and axonal protein transport in developing mouse hippocampal neurons. The authors demonstrated that embryonic hippocampal CA1 neurons with reduced VPS35 expression (via electroporation with microRNAs) display shortened apical dendrites, less dendritic spines and swollen commissural axons.…”
Section: Vps35 (Park17)mentioning
confidence: 99%
“…2). Later, studies showed that Vps35 depletion in neurons makes impairment of BACE1 retrieval and redistribution of BACE1 [59]. Sortilin, a Vps10p domain-sorting receptor, also participates in BACE1 retrograde trafficking.…”
Section: The Role Of Retromer Complex In Bace1 Traffickingmentioning
confidence: 99%